1998
DOI: 10.1083/jcb.140.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphin Functions as a Key Morphoregulator for Mammary Epithelial Cells

Abstract: Hepatocyte growth factor (HGF) and EGF have been reported to promote branching morphogenesis of mammary epithelial cells. We now show that it is epimorphin that is primarily responsible for this phenomenon. In vivo, epimorphin was detected in the stromal compartment but not in lumenal epithelial cells of the mammary gland; in culture, however, a subpopulation of mammary epithelial cells produced significant amounts of epimorphin. When epimorphin-expressing epithelial cell clones were cultured in collagen gels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
188
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(193 citation statements)
references
References 47 publications
5
188
0
Order By: Relevance
“…Previous studies have shown that epimorphin has morphogenetic effects on multiple epithelial tissues, including those of skin, hair follicle, lung, intestine, mammary gland, pancreas, gall bladder and liver. [4][5][6][7][8][9][10] In addition, several investigators have reported changes in the distribution of epimorphin-positive cells in inflammatory diseases of the lung and liver. [11][12][13][14] Epimorphin not only regulates morphogenesis but also functions as a mesenchymal regulator of epithelial repair.…”
mentioning
confidence: 99%
“…Previous studies have shown that epimorphin has morphogenetic effects on multiple epithelial tissues, including those of skin, hair follicle, lung, intestine, mammary gland, pancreas, gall bladder and liver. [4][5][6][7][8][9][10] In addition, several investigators have reported changes in the distribution of epimorphin-positive cells in inflammatory diseases of the lung and liver. [11][12][13][14] Epimorphin not only regulates morphogenesis but also functions as a mesenchymal regulator of epithelial repair.…”
mentioning
confidence: 99%
“…Isoforms of syntaxins 2 and 3, derived from alternative RNA splicing, have been identified previously (20,22,53,55). They all differ only in the COOH-terminal parts of the molecules, and our antibodies are predicted to react with all of them.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen assay-For 3D cell cultures in 3 mg/ml collagen, primary organoids or Eph4 cell clusters were embedded in type I collagen gels as previously described (Hirai et al, 1998). In brief, the Eph4 cells were preclustered in ultra low adhesion plates (Costar, Corning Life Sciences, Lowell, MA, USA) for 24 h, and then collected by differential centrifugation.…”
Section: Morphogenesis Assaysmentioning
confidence: 99%